2000
DOI: 10.1046/j.1365-2915.2000.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal range of Simulium neavei in an onchocerciasis focus of western Uganda

Abstract: The dispersal range of the vector Simulium neavei Roubaud (Diptera: Simuliidae) was investigated in an onchocerciasis focus in Kabarole district, western Uganda, adjacent to the Itwara Forest Reserve, where the species breeds in phoretic association with the river crab Potamonautes aloysiisabaudiae (Nobili) (Decapoda: Potamonautidae). Biting rates were highest at the edge of the forest, but blood-seeking flies were collected up to a distance of about 4 km from the forest. Entomological data did not agree with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 5 publications
2
13
0
Order By: Relevance
“…But dispersal of the infective Simulium flies from onchocerciasis-endemic areas into villages where investigated persons infected with Mansonella spp. were resident is unlikely because the only vector of O. volvulus in this region is S. neavei with a greatly limited dispersal range (Mpagi et al 2000a). The findings of this study support previous reports on the specificity of Ov20 protein in filarial infections (Bradley et al 1993;Nirmalan et al 1999).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…But dispersal of the infective Simulium flies from onchocerciasis-endemic areas into villages where investigated persons infected with Mansonella spp. were resident is unlikely because the only vector of O. volvulus in this region is S. neavei with a greatly limited dispersal range (Mpagi et al 2000a). The findings of this study support previous reports on the specificity of Ov20 protein in filarial infections (Bradley et al 1993;Nirmalan et al 1999).…”
Section: Discussionsupporting
confidence: 86%
“…were resident is unlikely because the only vector of O. volvulus in this region is S . neavei with a greatly limited dispersal range (Mpagi et al . 2000a).…”
Section: Discussionmentioning
confidence: 99%
“…9 Adult S. neavei require heavy forest canopy to survive and thrive. 10 The first studies of the Mount Elgon focus were conducted in the 1950s, when it was observed that there was a small extension of the focus into Kenya. 11 On the Uganda side of the border, vector control activities against S. neavei were carried out in 1957, largely to protect a proposed coffee research station.…”
Section: Introductionmentioning
confidence: 99%
“…However, dispersal can be wind-assisted and S. damnosum s.l. has been shown to disperse up to 500 km in west Africa when carried by seasonal monsoon winds (see Crosskey, 1990 for a review; but also see Mpagi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%